Small Heat Shock Proteins in Retinal Diseases - Rajeswaren, Vivian; Wong, Jeffrey O.; Yabroudi, Dana; Nahomi, Rooban B.; Rankenberg, Johanna; Nam, Mi-Hyun; Nagaraj, Ram H. (Frontiers in Molecular Biosciences, 2022)
This review summarizes the latest findings on small heat shock proteins (sHsps) in three major retinal diseases: glaucoma, diabetic retinopathy, and age-related macular degeneration. A general description of the structure and major cellular functions of sHsps is provided in the introductory remarks. Their role in specific retinal diseases, highlighting their regulation, role in pathogenesis, and possible use as therapeutics, is discussed.